Exploración de significados con respecto a la salud bucal de un grupo de gestantes de la ciudad de Medellín, Colombia ¿hay alfabetización en salud bucal? (2011)
ABSTRACT: In many cultures, mothers are responsible for taking care of their babies, being the mother frequently the most significant adult, a model to follow, and the principal transmitter of culture, including health knowledge and practices. The objective of this study was to explore a group of pregnant women’s perceptions of their own oral health and that of their children. These women were all from Medellín, Colombia, and they were participating in one of the city’s intervention programs. Methods: An ethno-methodological approach was used; therefore, semi-structured interviews were conducted, recorded, transcribed and analyzed, and the responses were classified according to four criteria: recurrence, divergence, tendencies, and significant meanings. Results: pregnant mothers give significant importance to the mouth due to survival and esthetic reasons. They emphasize teeth over other parts of the mouth and think that oral health is synonymous to healthy teeth. The concept of oral hygiene is represented as cleaning the teeth with toothbrush and toothpaste. The mouth of their future child is not a matter of concern, and they consider oral hygiene important but not in early stages. Conclusions: the interviewed mothers recognize the mouth as an essential survival element. Care of the baby’s mouth gains importance as teeth appear. Dental floss, which is considered necessary as a cleaning element, is not used by pregnant women, not is it frequent tooth brushing. The claim of Oral Health Literacy is to build knowledge in order to promote and preserve health.